2005
DOI: 10.1002/ajmg.a.30631
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic tetrasomy 14pter‐q13 due to a supernumerary isodicentric derivate of proximal chromosome 14q

Abstract: Tetrasomy of proximal 14q is an extremely rare condition and has never been reported to be associated with survival. We here report on the first case of mosaic tetrasomy of 14pter-q13 due to a de-novo supernumerary pseudoisodicentric chromosome in a 2-year-old boy with multiple dysmorphisms and malformations. The marker was detectable in nearly 25% of lymphocytes as well as in cells from buccal mucosa. Detailed fluorescence in situ hybridization (FISH) analyses allowed the characterization of the marker to ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
9
2
Order By: Relevance
“…Patients with idic(14)(q13) are rare, the present patient is the fifth case reported in the literature and the third live‐born (Table ) [Nuessle and Miles, ; George et al, ; Eggermann et al, ; Fdez‐Novoa et al, ; Schwanitz et al, ]. A spectrum of clinical features has been reported in association with partial tetrasomy 14q, and recurrent features include craniosynostosis, dysmorphic facial appearance with cleft lip and palate, coloboma of the iris, cardiac malformations and digital anomalies, as well as growth retardation and intellectual disability.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Patients with idic(14)(q13) are rare, the present patient is the fifth case reported in the literature and the third live‐born (Table ) [Nuessle and Miles, ; George et al, ; Eggermann et al, ; Fdez‐Novoa et al, ; Schwanitz et al, ]. A spectrum of clinical features has been reported in association with partial tetrasomy 14q, and recurrent features include craniosynostosis, dysmorphic facial appearance with cleft lip and palate, coloboma of the iris, cardiac malformations and digital anomalies, as well as growth retardation and intellectual disability.…”
Section: Discussionmentioning
confidence: 74%
“…Isodicentric chromosomes are supernumerary marker chromosomes that can be described as end‐to‐end duplications of centromere‐containing chromosomal material. When they occur in addition to 46 normal chromosomes, the result is a tetrasomy for the region involved [Eggermann et al, ]. Some recurrent isodicentric chromosomes, such as the idic(15) and the marker chromosome 22, are associated with specific syndromes while others occur rarely [McDermid and Morrow, ; Battaglia, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial trisomy 14 was also described in several reports from 40 yr ago [10-12]. Most of these patients were offspring of carriers of balanced translocations.…”
Section: Discussionmentioning
confidence: 70%
“…However, to our knowledge the mother and the DS child represent the first case of familial trisomy 14 (:p11-q11:) . The familial transmission of an extra sSMC 14(:p11-q11:) might be due to nondisjuction in both mother and the DS child, as small acrocentric chromosomes prone to nondisjunction, 10 Eggermann et al 11 reported mosaic tetrasomy of 14pter-q13 due to de-novo supernumerary pseudoisodicentric chromosome in a 2-yr-old boy with multiple dysmorphisms and malformations. The uniparental disomy of the 14q have been reported in various clinical conditions.…”
Section: Discussionmentioning
confidence: 97%